Anxiety and depression among hypertensive adults in tertiary care hospitals of Nepal. - Adhikari, Sangita (2021)
SUMMARY: The study was descriptive cross-sectional study exploring the anxiety and depression among hypertensive adults in tertiary hospitals of Nepal using a semi structured self-administered questionnaire. The sample for the study was 260. The data was entered in EPI DATA and analyzed by using SPSS version 22. p values <0.05 was considered as statistically significant. The mean age of the study participants above 18 years of age was 42.59 years. Age group 18-44 years constitutes maximum number of study participants. Among the 260 respondents, female participants were higher with 59.2% (154) whereas male were 106 in number constituting of 40.8%. Most of the participants were Brahmins (88) 33.8% followed by Chhetris (77) 29.6%.Similarly,233 ( 89.6%) patients were Hindu followed by Buddhist (19) 7.3%. About 46% of (121) patients did not have any symptoms of depressed mood and 73(28.1%) of the participants experienced the feelings of depressed mood only on questioning. Similarly, (151) 58.1% did not have feelings of guilt and 48(18.5%) participants who had feeling of guilt had let people down. Also, (210) 80.8% of hypertensive patient did not have thoughts of suicide and (21) 8.1% had thoughts of possible death while (4) 1.5% of patient d=has attempted suicide (142) 54.6%, (176) 67.7%, and (143) 55% of the patients experienced insomnia in early morning, mid night and early hours of the morning respectively. Among total of 260 respondents, the majority of participants (102) 39.2% had mild symptoms of anxious mood, followed by (86) 33.1% participants with moderate symptoms. Only (4) 1.5% participants had severe symptoms. Similarly, majority of participants (114) 43.8% had mild form of tension followed by (72) 27.7% with moderate tension while (43) 16.5% had no tension. Of the 260 respondents, majority of participants (123) 47.3% did not have fears, followed by (84) 32.3% of respondents with mild forms fears while only (4) 1.5% participants had severe form of fears. The majority of patients with hypertension (126) 48.5% had mild symptoms of insomnia, followed by (63) 24.2% without any symptoms of insomnia while (7) 2.7% participants had very severe insomnia.